THE DEVELOPMENT OF SOCIAL AND ECONOMIC ASPECTS OF THE RICE PRODUCTION CENTER (Study Case of Ampek Angkek and Kamang Magek of Agam District) - Fastabiqul Khairad (CV. Radja Publika, 2023)
West Sumatra province government enhancement the growth of rice production by developing rice production centers. The center’s purpose is to reduce cost and enhance efficiency which ultimately increases local economic growth. Kec. Ampek Angkek is a rice production center in the Agam district. In this case study, we explain the progress of center development set in 2013 of the social aspect and economic aspects inside and outside the production center. The research method used is qualitative descriptive with a case study approach. The condition of the development of social and economic use is a case to provide a detailed description of the development of the production center. The result showed that there were similar developments for each aspect